If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3(x + 20) = x Reorder the terms: -3(20 + x) = x (20 * -3 + x * -3) = x (-60 + -3x) = x Solving -60 + -3x = x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. -60 + -3x + -1x = x + -1x Combine like terms: -3x + -1x = -4x -60 + -4x = x + -1x Combine like terms: x + -1x = 0 -60 + -4x = 0 Add '60' to each side of the equation. -60 + 60 + -4x = 0 + 60 Combine like terms: -60 + 60 = 0 0 + -4x = 0 + 60 -4x = 0 + 60 Combine like terms: 0 + 60 = 60 -4x = 60 Divide each side by '-4'. x = -15 Simplifying x = -15
| 5(x-3)=-2 | | x^2+16x=105 | | 15x=5(x-14) | | 6-3x=4x-15 | | -2(x+15)=0 | | -2x(x+15)=0 | | 2x-7=38-x | | 8x-(6x-5)=21 | | 3x-7=x-17 | | 2p-2(5-4p)=5(p-5)-35 | | 3x-7=x-7 | | 10x+2=-4 | | 9x+1=7X+29 | | 15+3x=51-3x | | 20-[2+5y-3(y+5)]=-5(5y-3)-[8(y-1)-26y+10] | | 5x+16=3x+60 | | v^2(4v^2+22v^5+12)=0 | | 3x-7=-3x+5 | | H=50t-5t^2 | | 36(2x-1)=6(x+5)+3x | | 8x+1=-2 | | 3(x+4)-2x-8=5 | | 10=7x-25 | | H=-5t^2+20t+2 | | 23-13= | | 6x+1=5.2 | | 2w^2+9w+38=(w+6)(w+6) | | t=(v-u)a | | 63=9(Y) | | 2+2+2+2+2+2= | | x^2-3x=2(x-1) | | 63=9TIMESY |